Addressing Social Justice in the Science Methods Classroom through Critical Literacy: Engaging Preservice Teachers in Uncomfortable Discussions - Bautista, Nazan; Batchelor, Katherine E. (Innovations in Science Teacher Education, 2020)
The purpose of this paper is to exemplify how teacher candidates can be engaged in discussions around social justice and equity in science methods courses while also learning about and practicing essential science teaching strategies and skills. Our aim is that science teacher educators who do not feel confident enough to explicitly address these important issues in methods courses are encouraged to think creatively about how they can modify or alter their current practices in a way to prepare science teachers for the changing demographics of science classrooms. We present an engineering design activity that is coupled with critical literacy skills, called ‘Build a Child.” Upon identifying the problem, we introduce the context of the preservice teachers’ science methods course and reason for this work, followed by defining critical literacy and how it pairs well in science education. We then share the “Build a Child” engineering project and how we asked preservice teachers to critique and reflect on their creations, thus bringing in a critical literacy framework to the curriculum. Next, we share three findings based on our data analysis, and we end with the importance of science methods courses implementing social justice education and suggestions on how to reexamine our science curriculum to make it more culturally relevant and equitable for all students.